(untitled) (The Research of Medical Science Review, 2025)
Background: Intrahepatic cholestasis of pregnancy (ICP) is the pregnancy-specific liver disorder characterized by pruritus and elevated bile acids, which can raise danger of serious maternal and perinatal results. Limited data exist regarding its prevalence and outcomes in our local population, necessitating further investigation.Aim: This article aimed to assess maternal and serious results associated with ICP in a large population of pregnant women presenting to the Obstetrics and Gynecology Department of PAF Hospital, Islamabad.Methods: A cross-sectional study was led at PAF Hospital, Islamabad, from November 2024 to January 2025. Using the WHO sample size calculator, a minimum of 370 participants were included, based on a 4% prevalence of ICP in the local population, 95% confidence interval, and a 2% margin of error. A non-randomized consecutive sampling technique was employed for patient selection. Data on maternal and fetal outcomes were collected and analyzed using SPSS version 26.0.Results: The study included 370 pregnant women diagnosed with ICP. Maternal complications observed included an increased incidence of preterm labor, gestational hypertension, and cesarean section rates. Adverse fetal outcomes included meconium-stained amniotic fluid, fetal distress, and an elevated risk of stillbirth. The statistical analysis revealed a significant related among elevated bile acid levels and adverse perinatal outcomes.Conclusion: ICP was corelated through an enlarged danger of maternal and fetal complications, emphasizing the need for early diagnosis and close monitoring. The findings underscore significance of routine bile acid screening and timely interventions to optimize perinatal outcomes.